A Three-Dimensional Hyaluronic Acid-Based Scaffold Model for Electroporation-Enhanced Resveratrol Therapy in Triple-Negative Breast Cancer - Pragatheiswar Giri; Monica Dettin; Annj Zamuner; Maria Teresa Conconi; Ignacio G. Camarillo; Nicolò Martinelli; Luigi Dall’Olmo; Elisabetta Sieni; Raji Sundararajan (Cell Biochemistry and Biophysics, 2026)
Triple-negative breast cancer (TNBC) is an aggressive malignancy defined by the absence of estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2). These molecular characteristics render targeted therapies less effective and contribute to poor clinical outcomes. Towards this, we studied the electroporation-mediated delivery of resveratrol, a polyphenolic compound with pleiotropic anticancer activities, on MDA-MB-231, human TNBC cell line. Both conventional two dimensional (2D) monolayer cell culture and three-dimensional (3D) hyaluronic acid HA-EAbuK-IKVAV scaffold-based cell cultures were used. Two electroporation (EP) protocols (EP1: 8 pulses, 800 V/cm, 100 µs at 1 Hz; EP2: 8 pulses, 1000 V/cm, 100 µs at 1 Hz) were evaluated for their effects on cytotoxicity and reactive oxygen species (ROS) generation. In 3D, the combined treatment similarly reduced viability to 20% (EP1 + Resv) and 17% (EP2 + Resv), whereas in 2D, the viability reduction is 24% and 18%, respectively. Mechanistically, ROS levels increased substantially with the combination treatment: in 2D, ROS rose to 3 times (EP1 + Resv) and around 3.5 times (EP2 + Resv) the control, while in 3D, ROS increased to 2.4 times (EP1 + Resv) and 2.9 times (EP2 + Resv). Moreover, the combined treatment of electroporation and resveratrol administration on 3D HA-EAbuK-IKVAV-cultured cells decreased the expression of cell cycle regulatory protein Cdk2 and proliferation marker Ki67. These findings highlight the importance of 3D microenvironmental cues in modulating TNBC responsiveness to resveratrol and underscore the potential of combining electroporation with natural compounds as a rational therapeutic strategy for this challenging subtype of breast cancer.